The cost of sprawl: an Italian case study - Laura Fregolent; Stefania Tonin (European Regional Science Association (ERSA), 2010)
In this paper we describe and analyze an Italian case of urban sprawl and its urban growth for understanding the development of a "metropolitan sprawled system". The portion of Veneto Region that is part of our case study cover about 3700 square km, for a total of 145 municipalities. The manifestations of physical and morphological sprawl came as a result of specific cultural and political situations and economic development, such as rising incomes, and were also facilitated by the local topography. The most important changes occurred in this area over the past 30 years, starting from the 1970's: between 1970 and 1990, the population increased somewhat, but the urbanized and developed land area increased significantly. The main aim of our paper is to find out if low-density development patterns are more expensive and if local public spending is influenced by different urban forms expansions. We measure sprawl with some indicators suggesting in the literature such as urban density, population density and the territorial fragmentation. Data for the economic analysis come from local balance sheets of 145 municipalities for the year 2007. In particular, we collect the costs of the main public services sustained by the municipalities such as public transport, road and street maintenance, waste management, and water and sewer services. Adopting regression analysis, we estimate the impact of urban sprawl on different current expenditures, controlling for other variables such as local taxes paid by citizens, central government aids, territory characteristics, and more others. We find that low density development patterns are in general more expensive, in particular when municipalities have to provide education services, solid waste collection and other environmental and urban management services. Our analysis wants to highlight the threats pose by sprawl in terms of urban sustainable development patterns and to put in evidence the costs of an unbalanced growth in order to let public government to re-orient their policies versus the containment of the urban growth process.
Keywords: 330; urban sprawl; local public spending; regression analysis